Regeneración pulpar en dientes maduros usando células madre, una revisión narrativa (2021)
At present, conventional endodontics is a procedure that presents a variety of side effects in the future, that is why pulp regeneration and/or revascularization therapies are developed, which are usually performed in immature permanent teeth in order to generate more conservative treatments. In recent years and in the recent advances in tissue engineering, a way has been registered for pulp therapy that allows us the complete pulp regeneration of mature teeth, in which advantage is taken of the differentiation capacity of residual pulp stem cells. These cells are capable of generating a highly vascularized living tissue rich in connective tissue, which colonizes the available pulp space. However, until the completion of this review, no method has been reported in the literature as viable for clinical application in humans.